2005
DOI: 10.1097/01206501-200506000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Clinical Pattern of Parthenium Dermatitis: A Study of 74 Cases

Abstract: Our aim was to study the evolution of clinical pattern of parthenium dermatitis. Patients with clinical picture consistent with parthenium dermatitis for 3 years or more along with positive patch test to parthenium were studied. Patients were questioned regarding the site(s) of dermatitis at the onset and change in localization in the following years. Patients were classified into airborne contact dermatitis, chronic actinic dermatitis (CAD) pattern or mixed pattern dermatitis. There were 74 patients (49 men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
(15 reference statements)
2
16
1
Order By: Relevance
“…Previous studies have described an evolution of the clinical pattern of parthenium dermatitis from the ABCD pattern to the CAD‐like pattern. The CAD‐like pattern was predominant in our study .…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have described an evolution of the clinical pattern of parthenium dermatitis from the ABCD pattern to the CAD‐like pattern. The CAD‐like pattern was predominant in our study .…”
Section: Discussionsupporting
confidence: 60%
“…Most of the allergens identified were in an occupational setting, if not the references are indicated with asterisk (Table 1). As in other recent reviews (2, 15, 16) plants represent a very important cause, particularly the Asteraceae (Compositae) family, for which recent advances in investigation of the clinical signs, diagnosis, and therapy have been published (17, 18*, 19*, 20, 21). Although mono‐ and sesquiterpene‐lactones, contained in Asteraceae, are by far the most frequently described airborne allergens in weed dermatitis, many other plant and wood allergens remain unidentified.…”
Section: Causes Of Airborne Dermatosisamentioning
confidence: 98%
“…Various national and international authors have reported parthenium dermatitis simulating photodermatitis. Sharma et al [2] reported a series of 74 PD patients wherein 60 patients presented as ABCD, 9 as CAD, and 5 as mixed pattern. Of the 60 patients who presented as ABCD, 27 changed to CAD pattern and 11 to mixed pattern after an average period of 4.2 years.…”
Section: Discussion Discussionmentioning
confidence: 98%
“…Sharma et al in their study found 3/9 photopatch tested patients with photoallergic reaction to parthenium and another three patients showed photoaggravation. [2] The prevalence of plant sensitivity in CAD was reported to be 47/55(85.5%) in a study from Canada. [9] However, Somani reported 3/9 (33.3%) CAD patients with parthenium sensitivity with 2/9 (22.2%) patients showing photoallergy to parthenium.…”
Section: Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation